Employee engagement of Santa Ana Hospital health staff and its association with their job performance - Gonzales, Kristine S.
Human resource is important in any organization or program. They mobilize in implementation and conduct of operational process, deliver health services, and evaluate its effectiveness. They also help in reducing barriers to achieve organizational goals. Therefore, the performance of health workers is one of the factors in the success in the delivery of health services. However, in recent years patient dissatisfaction of Santa Ana Hospital increases with increasing demand and limited resources, any organization will operate best when they give importance to their employee?s enagement to their operation. This research study aimed in investigating the factors that affect job performance of health staff at Santa Ana Hospital. The study adopted a cross-sectional design with quantitative component. Total enumeration of participants was taken for the study. Data was collected through self-administered questionnaire and job performance evaluation form. It employed descriptive statistics methods for presenting and summarizing demographic profile of the participants. Bivariate analyses between variables will be performed using Fisher Exact Probability Test to know significant association. In total of 125 respondent, most of the respondents (54 out of 43.2%) were classified as engaged followed by barely engaged (41.6%), and highly engaged (14.4%). Only 0.8% or 1 out of 125 health staff was classified as unengaged. The research findings also indicate that the workplace factors such as organizational culture, job satisfaction and competencies influence employee engagement. Thus, a meaningful workplace environment that culminates harmonious organizational culture, satisfied and equipped employees boost employee engagement. It also shows that employee engagement is significantly associated with the job performance of Santa Ana Hospital health staff (p value <0.001). Thus it shows that engaged employees perform better compared to an unengaged employees. Hence level of engagement matter because it can correlate with job performance and other organizational benefits.